The importance of oral communications among UPM business students - Mohd Salleh, Lailawati; Mohd Noah, Sidek (Universiti Putra Malaysia Press, 2000)
In this short study, business students in Universiti Putra Malaysia were requested to respond to a set of questionnaires pertaining to their awareness of the importance of oral communication. Also, there were questions on their use of these skills when conveying messages and other information on how they acquired these skills. Results of the study show that business students in Universiti Putra Malaysia are aware of the importance of these skills and in fact, they use these skills when communicating. The study also revealed that they had acquired the skills from watching television, videos, real life speeches; communication books and, comments from friends.